Distribution of shear stress in smooth rectangular open channel - Tan, Swee Yen (Universiti Malaysia Sarawak, UNIMAS, 2010)
The study of shear stress distribution is an important element in most hydraulic design field. A knowledge of the shear stress distribution helps in understanding of the mechanics flows and also solving certain problems such as sediment transportation and design of stable channels. The objective of this research is to study the distribution of the shear stress in smooth rectangular open channel. All the experimental work was conducted using the available open channel in Civil Engineering Hydrology Laboratory. The Stokes (1845) local wall shear stress formula will be use to determine the distribution of the shear stress in the open channel. Similar equation used for determining the local wall shear stress will be use to study the bed shear stress. Based on the result obtained, the results from this method are compared with theoretical statements in literature review. The results show that the increment of shear stress depends on the position of local velocity from the solid boundary of the open channel. This shows that higher shear stress results in reduction of local velocity.